How Can a Ketogenic Diet Improve Motor Function? - Veyrat-Durebex, Charlotte; Reynier, Pascal; Procaccio, Vincent; Hergesheimer, Rudolf; Corcia, Philippe; Andres, Christian R.; Blasco, Hélène (Frontiers in Molecular Neuroscience, 2018)
The ketogenic diet (KD) is a normocaloric diet composed by high fat (80-90%) and low carbohydrate and protein that induce fasting-like effects. KD increases ketone bodies (KB) production and blood concentration, providing to the brain an alternative energy supply that enhance oxidative mitochondrial metabolism. In addition to its profound impact in the neuro-metabolism and bioenergetics, the neuroprotective effect of specific polyunsaturated fatty acids and KB involves pleiotropic mechanisms such as the modulation of neuronal membrane excitability, inflammation or reactive oxygen species production. KD is a therapy used for almost a century to treat medically intractable epilepsy and is increasingly explored in numbers of neurological diseases. Motor function has also been shown to be improved by KD and/or medium chain triglyceride diets in rodent models of Alzheimer’s disease, Parkinson’s disease, amyotrophic lateral sclerosis and spinal cord injury. These studies showed that KD may induce a modification in synaptic morphology and function, involving ionic channels, glutamatergic transmission or synaptic vesicular cycling machinery. However, little is known about the molecular mechanisms underlying the impact of KD on motor function and the perspectives of its use to afford the neuromuscular effects. The aim of this review is to explore the conditions through which KD might improve motor function. In a first part, we will describe the main consequences of KD exposure in tissues involved in motor function. Then we will report and discuss the relevance of KD in pre-clinical and clinical trials in the main diseases presenting a motor dysfunction.